Financial Development and Economic Growth : An Overview - Khan, Mohsin (IMF Working Papers; Working Paper, 2000)
In recent years there has been substantial theoretical and empirical work on the role that financial markets play in fostering economic growth and development. This paper provides a selective review of the literature, as well as new empirical evidence on the relationship between financial development and economic growth for a large cross-section sample of countries. While the results indicate that the effect of financial development on growth is positive, the size of the effect varies with different indicators of financial development, estimation method, data frequency, and the functional form of the relationship.